2020
DOI: 10.1089/bio.2020.0003
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Microfiber Encapsulation Enhances Cryopreservation of Human Red Blood Cells with Low Concentrations of Glycerol

Abstract: Cryopreservation of red blood cells (RBCs) has been studied as a typical example of cryobiology methodology. To date, a mature and long-term cryopreservation process for RBCs has been developed, which has the weakness of complicated procedures due to high concentrations of glycerol (Gly). Therefore, it is still a research focus to find a new method for cryopreservation of RBCs to reduce the concentrations of cryoprotectants (CPAs). In this study, alginate hydrogels, which have been widely used in preservation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…So far, we have demonstrated that poly­( d / l -serine) is water-soluble, biodegradable, and non-cytotoxic, making it a desirable biomedical polymer and probably can be used as the PEG alternative with degradability and functional groups. Here, we took RBC cryopreservation ,,− as an example to illustrate the potential biomedical applications of poly­( d / l -serine). A series of recrystallization experiments were carried out with the “splat-cooling” assay , to investigate the IRI activity of poly­( d / l -serine) (Figures a and S8–S10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, we have demonstrated that poly­( d / l -serine) is water-soluble, biodegradable, and non-cytotoxic, making it a desirable biomedical polymer and probably can be used as the PEG alternative with degradability and functional groups. Here, we took RBC cryopreservation ,,− as an example to illustrate the potential biomedical applications of poly­( d / l -serine). A series of recrystallization experiments were carried out with the “splat-cooling” assay , to investigate the IRI activity of poly­( d / l -serine) (Figures a and S8–S10).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the cryopreservation of blood has become an urgent need because of the sizable demand and the short survival time (42 days at most) without cryopreservation and in complex isotonic solutions. According to previous reports, the extracellular ice formation (ice recrystallization) during the thawing process is one of the major reasons causing cell death. In order to solve this problem, a lot of synthetic materials such as glycopeptides, peptides, polymers, , hydrogel microfiber, and some other nano materials with specific ice recrystallization inhibition (IRI) activity and a good cryoprotective effect have been reported. However, the toxicity and biodegradability of these synthetic materials remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The mixed RBC hematocrit was ∼40%. The RBC–CPA hybrid solution flowed out from the concentric inner chamber of the tube-in-tube device (23 G, inlet 1) and the outer chamber (17 G, inlet 2) for 2% sodium alginate outflow . As the concentric droplets at the tip of the needle flowed out, they were broken up into microdroplets by the electric field generated from a high-voltage generator.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, Zhao et al first reported hydrogel microencapsulated porcine adipose-derived stem cells and successfully achieved low-concentration CPA vitrification. In a later study, they successfully combined magnetic warming with hydrogel microencapsulation, achieving low-CPA vitrification cryopreservation of stem cells. , Additionally, Tian et al developed an ultrafine hydrogel microfiber encapsulation system to successfully achieve low-concentration and low-toxicity vitrification . Cao et al used hydrogel microfiber encapsulation of RBCs and successfully enhanced the recovery of RBCs at a low concentration of glycerol . However, microencapsulation of RBCs has not been reported thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogel fibers have emerged as promising scaffolds in materials science, cell biology, and tissue engineering for their large specific surface area, excellent biodegradability, and flexible mechanical properties. Hydrogel fibers are widely used in transplant carriers, , drug delivery, and hydrogel sensors, , which are produced by coating, electrospinning, , bioprinting, and microfluidics . In recent years, the microfluidic technique has been utilized as a versatile tool to fabricate the hydrogel fibers with various structures, compositions, and functions due to the flexibility of chip design and the accuracy of flow control .…”
Section: Introductionmentioning
confidence: 99%